Routing in distributed cognitive radio networks: A survey - Al-Rawi, Hassan A. A. *; Yau, Alvin Kok-Lim * (Springer US, 2013)
Cognitive Radio Networks (CRNs) have been receiving significant research attention recently due to their ability to solve issues associated with spectrum congestion and underutilization. In a CRN, unlicensed users (or Secondary Users, SUs) are able to exploit and use underutilized licensed channels, but they must evacuate the channels if any interference is caused to the licensed users (or Primary Users, PUs) who own the channels. Due to the dynamicity of spectrum availability in CRNs, design of protocols and schemes at different layers of the SU’s network stack has been challenging. In this article, we focus on routing and discuss the challenges and characteristics associated with it. Subsequently, we provide an extensive survey on existing routing schemes in CRNs. Generally speaking, there are three categories of challenges, namely channel-based, host-based, and network-based. The channel-based challenges are associated with the operating environment, the host-based with the SUs, and the network-based with the network-wide SUs. Furthermore, the existing routing schemes in the literature are segregated into three broad categories based on the relationship between PUs and SUs in their investigation, namely intra-system, inter-system, and hybrid-system; and within each category, they are further categorized based on their types, namely Proactive, Reactive, Hybrid, and Adaptive Per-hop. Additionally, we present performance enhancements achieved by the existing routing schemes in CRNs. Finally, we discuss various open issues related to routing in CRNs in order to establish a foundation and to spark new interests in this research area.